2017
DOI: 10.4149/neo_2017_316
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum gamma-glutamyltransferase levels in patients with hepatocellular carcinoma

Abstract: Here we assessed the predictive value of gamma-glutamyltransferase (γ-GT) for the prognosis of patients with HCC and compared the γ-GT with other prognostic factors. We retrospectively analyzed outcomes for 858 patients first diagnosed with HCC. Cox univariate and multivariate analyses receiver operating characteristic (ROC) curve were used for the study of significance of prognostic factor. A Kaplan-Meier survival analysis was performed to assess the value of γ-GT as an HCC prognostic factor in different clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As an almost ubiquitous enzyme, γ-glutamyltransferase (γ-GT) initiates the degradation of extracellular glutathione and is also conjugates and correlates with biotransformation, nucleic acid metabolism, and oncogenesis [5]. Previous studies have shown that high levels of γ-GT are significantly associated with unfavorable prognoses in HCC patients [6, 7]. Prealbumin (PA), which is synthesized by the liver, is a recently identified biomarker indicative of liver synthetic functions and has not been included in the traditional Child-Pugh classification system.…”
Section: Introductionmentioning
confidence: 99%
“…As an almost ubiquitous enzyme, γ-glutamyltransferase (γ-GT) initiates the degradation of extracellular glutathione and is also conjugates and correlates with biotransformation, nucleic acid metabolism, and oncogenesis [5]. Previous studies have shown that high levels of γ-GT are significantly associated with unfavorable prognoses in HCC patients [6, 7]. Prealbumin (PA), which is synthesized by the liver, is a recently identified biomarker indicative of liver synthetic functions and has not been included in the traditional Child-Pugh classification system.…”
Section: Introductionmentioning
confidence: 99%
“…The γ-GT level, in particular, has critical clinical significance as an indicator of prognosis 33,34. This indicator helps to predict prognosis and helps with the selection of further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as a reflection of the inflamed liver microenvironment in patients with chronic hepatitis [43], γ-GT may be an attractive predictor for the prognosis of HCC patients. In a recent study, the prognostic value of γ-GT ≥ 75 U/L was shown to be higher than that of Child-Pugh staging, MELD and serum AFP [44].…”
Section: Analysis Of Angiogenetic Biomarkers In Patients With Hepatocellular Carcinoma and Correlation With Clinical Parametersmentioning
confidence: 92%